The Effect Of Placement, Workload And Competence On Employee Performance At Pt. Pln (Persero) Up3 Pematangsiantar - Afdol, Riyadi; Wahyuningtyas, Ratri (International Journal of Science, Technology & Management, 2025)
This study aims to analyze the placement, workload and competency and performance of employees at PT. PLN (Persero) UP3 Pematangsiantar and analyzed the influence of placement, workload and competence on employee performance at PT. PLN (Persero) UP3 Pematangsiantar. This research is a quantitative research with a descriptive approach with the research population is all employees at PT. PLN (Persero) UP3 Pematangsiantar as many as 141 people. Descriptive data analysis using Structural Equation Modeling - Partial Least Square (SEM-PLS). The findings of the study show that a) There is a positive and significant influence of placement variables on performance that has a significant effect on performance. b) There is a negative and significant influence of workload variables on performance. c) There is a positive and significant influence of competency variables on performance.